Potential of seaweed (Eucheuma cottonii) supplementation to reduce methane production, improve fermentation, and modulate the microbial composition of forages and crop by-products during in vitro rumen fermentation - Widiawati, Yeni; Widodo, Slamet; Adegbeye, Moyosore Joseph; Saputra, Ferdy; Alvarado-Ramírez, Edwin Rafael; Sánchez Guerra, Nadia Alejandra; Anggraeny, Yenny Nur; Puastuti, Wisri; Yulistiani, Dwi; Rohaeni, Eni Siti; Handiwirawan, Eko; Praharani, Lisa (Frontiers in Veterinary Science, 2025)
IntroductionIn Indonesia, small-scale livestock farmers commonly feed their animals with forage resources that are high in fiber and low in digestibility, which contributes to increased methane (CH4) production in ruminants. To address this issue, algae, including marine species, have shown significant potential to improve rumen fermentation profiles, modulate microbial composition, and reduce CH4 emissions in these animals. Therefore, the aim of the present study was to evaluate the impact of supplementation with the marine seaweed Eucheuma cottonii on total gas and CH4 production, degradability, fermentation end-products, and rumen microbial composition in forages and crop by-products, using an in vitro system.MethodsThe forages and crop by-products evaluated were buffel grass (GB; Cenchrus ciliaris), elephant grass (EG; Pennisetum purpureum), rice straw (RS), corn stalk (CS), oil palm leaves (PL), and sugarcane leaves (SC). Seaweed supplementation was carried out by replacing a proportion of the dry matter (DM) in the basal diet corresponding to each forage or crop by-product, with inclusion levels of 0, 4, 8, and 12%, calculated on a DM basis. The forages and crop by-products were obtained from local farms in Serang and represent the most commonly used basal feed sources for ruminants by small-scale farmers and industry stakeholders. Seaweed was collected during the dry season, in July 2021, 45 days after planting, from a cultivation site located in Serang, Banten, Indonesia.Results and discussionResult showed that corn stalk produced the highest asymptotic gas, dry matter digestibility, shorted fermentation lag time, SCFA, metabolizable energy, and microbial crude protein. Corn stalk production the highest asymptotic (p < 0.001) methane gas, but had the lowest proportion of methane gas compared to total gas. Microbial analysis showed that rice straw without seaweed had the highest microbial diversity and evenness while rice straw with 8% seaweed group, exhibited lower methanogen abundance, increased Rikenellaceae_RC9 gut group and Ruminobacter. Cornstalk was the most efficient forage in rumen fermentation, while E. cottonii supplementation modulated fermentation, enhanced microbial protein synthesis, reduced methane emissions, and altered microbial diversity. Therefore, corn stalks without seaweed is a highly effective crop-by product for ruminant nutrition offering better fermentation characteristic and energy yield.